Anti-cancer activity of Conyza blinii saponin against cervical carcinoma through MAPK/TGF-β/Nrf2 signaling pathways. (6th April 2020) - Peng, Lei; Hu, Chenxi; Zhang, Chaozheng; Lu, Yingying; Man, Shuli; Ma, Long
Abstract: Ethnopharmacological relevance: Conyza blinii H.Lév. is a type of natural plant distributed in southwest of China. Its dried overground section can be used in traditional Chinese medicine (TCM) for treating infections, inflammations and occasionally cancers. CBS ( Conyza blinii saponin), mainly composed of triterpenoidal saponins of Conyza blinii H.Lév. CBS is considered as the major active fraction of this species. The current investigation have focused on the mechanisms of CBS with regard to its anti-cancer activity. Hence it is of high relevance of identifying the anti-cancer efficacy of ethnomedicine. Aim of the study: To understand the anti-cancer mechanism of CBS using both in vitro and in vivo experiments. Materials and methods: CBS ( Conyza blinii saponin) was obtained as described previously. We tested the anti-cancer activity of CBS using in vitro HeLa cell models and in vivo animal models. We adopted immunoblot, RT-PCR (reverse transcription polymerase chain reaction), luciferase reporter assay and flow cytometry to study relevant proteins, genes, pathways and cellular ROS (reactive oxygen species) responsible for anti-cancer activity of CBS. More, 24 tumour-xenografted mice were grouped randomly as 'control', 'cisplatin' (as positive control), 'low dose' and 'high dose' groups. The IL-1β, TNF-α, PGE2 and IL-2 in the blood serum and the tumour tissue of mice were measured. Results and conclusions: We have found that CBS is capable of inducing apoptotic cancer cell death via both caspase-dependent and -independent pathways. CBS inhibits the activation of TGF-β signaling pathway in a dose- and time-dependent manner. Phospho-ERK, phospho-JNK and phospho-p38 MAPK are significantly suppressed by CBS. Furthermore, some inflammation mediators including IL-1β, TNF-α and PGE2 from animal samples were found decreased in CBS-treated mice models. In contrast, the level of IL-2, a cytokine commonly used for treating cancers, increased reversely. Last, we have discovered that CBS is able to decrease the expression of Nrf2, inhibit the activation of ARE and increase ROS level in HeLa cells. In summary, we have confirmed that the anti-cancer activity of CBS is possibly related to its TGF-β, MAPK, Nrf2 signaling pathways as well as some cancer related inflammation mediators and cytokines. Graphical abstract: Image 1